A journey through the paintings of Jacopo Torni: characteristics and hypotheses - Liliana Campos Pallarés (Cuadernos de Arte de la Universidad de Granada, 2011)
The pictorial work of Jacopo Torni, artist known most of all for his architectonic works and sculptures, is still full of unknowns. This work reviews his career in the field of painting and analyses the different views of the specialists about his documented creations and those attributed to him, in order to shine a light on the most obscure production of the Florentine artist.